Simulation and Experimental Studies of Fto/Wo3 and Fto/Wo3/Ag Thin Film Structures for Electrochromic Analysis Deposited by Dc & Rf Magnetron Sputtering - Radhalayam, D (Springer, 2024)
In this work, DC & RF magnetron sputtering and COMSOL multiphysics were used to simulate and deposit WO3 and WO3/Ag films, respectively. In the simulation cyclic voltammetry (CV) analysis was examined. The current density for the WO3/Ag films in comparison to the WO3 film was displayed higher. Based on the simulation findings, the experiment was done using DC & RF magnetron sputtering to deposit WO3 and WO3/Ag films. Scanning electron microscopy (SEM), X-ray diffraction (XRD), UV–vis spectrometer, and electrochemical analyzer were used to examine the structural, morphological, EC, and optical characteristics of the deposited films. The SEM study revealed a smooth surface for WO3 films and WO3/Ag shows the grain of silver film. The XRD analysis of WO3 films shows the amorphous nature and in WO3/Ag films silver peaks were shown. The bandgap values were found to be 3.14 eV and 3.02 eV for WO3 and WO3/Ag films, respectively. Comparing the WO3/Ag film to the WO3 film, the cyclic voltammograms showed that the WO3/Ag film had the maximum current. In comparison to the WO3 film (30 cm2C−1), higher coloring efficiency values were noted for the WO3/Ag film (48 cm2C−1). For the WO3/Ag film, less time is needed for the coloring (tc = 2.2) and belching (tb = 1.8 s). It was clear that compared to a single-component WO3 film, the Ag-embedded WO3 composite system performed noticeably better electroactively and electrochemically. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.